Study on proximate composition and nutritional quality of some farm made fish feed collected from Muktagacha, Trishal and Phulpur upazila in Mymensingh district - Toppo, Narayon; Rana, Md Masud; Rahman, Md Mamunur; Hossain, Md Sazzad (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
An experiment was conducted to evaluate the feed quality of farm made feed from three upazila of Mymensingh district for four months from July to October, 2015. Fish feed samples were collected from various farms at Muktagacha, Phulpur and Trishal upazila of Mymensingh district. Total 30 feed samples were analyzed to determine the proximate composition and quality of farm made feed. Only one feed sample (F- 27) contains less than 12% moisture found in Trishal upazila. Maximum moisture value (24.53%) was found in feed sample F-13 in Phulpur upazila which indicated that this feed is poor quality compared to others. These may due to lack of maintenance at processing and may be due to improper storage system. Only four feeds were found having more than 25% protein. The analyzed crude protein contents of fish feed varied from 10.85 to 27.30%. The highest protein content was observed in feed (F-20) (27.30%) and the lowest was found in 10.85% in feed (F-22). The mean crude lipid values of the analyzed fish feeds varied from 5.79 to 22.95%. Highest lipid content was observed in 22.95% in feed (F-19). The analyzed mean ash content of fish feeds varied from 8.41 to 20.99%. The fiber content was observed within 4.35-8.20%. Ash content of feed (F-22) was found higher (20.99%) than other feeds. The analyzed nitrogen free extract (soluble carbohydrate) content of farm made fish feeds varied from 18.62 to 43.25%. The highest nitrogen free extract containing feed (F-25) having 43.25% NFE. The findings of this study demonstrated that low quality feeds and ingredients were supplied to the fish farmers by majority of feed traders and the farms with few exceptions were bound to use those ingredients due to their manufacture constraints. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 1-8